A study on the migratory pathways of schistosoma japonicum from the pulmonary circulation to the portal vein of white mice. - Garcia, Rosario G.
The path of migration of Schistosoma Japonicum from the lungs to the liver was studied by exposing the white mouse to approximately 100 cercariae from crushed Oncomelania Quadrasi. The purpose of which is to determine whether the worms after reaching the lungs go to the pulmonary veins to the heart and arterial circulation, pass through the capillaries of the gastro-intestinal tract into the portal and mesenteric veins where they grow into adult stage, or by tissue migration to the diaphragm, liver and the portal and mesenteric veins. At daily intervals up to the 30th day after exposure, worm counts were done on pleural and peritoneal cavity washings, lung-heart, liver and mesenteric perfusates. The lungs, diaphragm and liver of some of the mice were taken for histopathological studies. The results of this study supported the view of tissue migration. Evidences were the presence of many petechial hemorrhages in the lungs during the period of larval migration indicating that worms leave the pulmonary circulation, presence of young schistosomules in the pleural and peritoneal cavities, significant tissue reactions in the lungs, diaphragm and liver and the absence of hemorrhages in the Gastro-intestinal tract capillary beds. Worm counts of lung-heart perfusates did not reveal significant numbers to support the view that they travel via circulation to reach the liver. Worm count results of the liver and mesenteric perfusates, however indicated that the worms travelled via tissue migration since liver perfusates revealed worms only after pleural washings became positive for parasites and before the mesentric perfusates started to show worms.
Thesis (Master of Science in Public Health, Parasitology)--University of the Philippines Manila.
Keywords: Schistosoma japonicum